Antibacterial activity of artonin e and lysicamine against multi-drug resistant staphylococcus aureus isolates / Asdren Zajmi - Asdren, Zajmi (2015)
Infectious diseases are one of leading causes of death world-wide and there is a growing need for new anti-infective agents to combat multi-resistant strains of bacteria. One of the major pathogens which is responsible for many infective and systemic infections in the health care and community settings is Staphylococcus aureus. In many cases there are increasing of resistant to antibiotics and potential relapse of disease with the current antimicrobial therapy protocols. Thus there is a need for additional and alternative antibacterial agents for the treatment of diseases caused by this pathogenic bacteria. Natural plant products are promising sources of novel antimicrobial compounds. In the present study, an investigation on the antibacterial activity of natural plant compounds is presented. In this study, we report on the antibacterial activities of artonin E, a prenylated flavonoid compound isolated from Artocarpus elasticus and lysicamine, an oxoaporphine alkaloid isolated from leaves of Phoebe grandis evaluated against gram-positive S. aureus including methicillin-resistant Staphylococcus aureus (MRSA). Both compounds artonin E and lysicamine demonstrated generally strong and comparable antibacterial activity with the commonly used antibiotics against S. aureus and methicillin-resistant Staphylococcus aureus (MRSA) isolates with MICs of less than 4 ug/mL and 8 ug/mL respectively. The time killing curves for S. aureus treated with both compounds revealed rapid death with a decline in viable counts (>3 log10 CFU/mL) of S. aureus. Electron microscopy showed that both artonin E and lysicamine were rapidly incorporated by both bacterial isolates. The excellent bactericidal activities demonstrated by artonin E and lysicamine make them attractive candidates for further development of antibacterial agent research.